A case of mucin-producing cholangiocarcinoma with invading the abdominal wall - KOJIMA, Kuniaki; BEPPU, Tomoe; MATSUMOTO, Kouji; SATOH, Yasunari; FUTAGAWA, Shunji; KOSAKA, Taijirou; TAKAMORI, Shigeru; SUDA, Kouichi; NAMEKATA, Kouji; FUKASAWA, Masaki; SUGOU, Hiroyuki; SUZUKI, Kunimi (Tando, 2000)
The patient was a 72-year-old female who had a chief complaint of palpable abdominal wall mass. According to her medical records, she had undergone laparocholecystectomy for cholelithiasis, and choledochotomy and EST for choledocholithiasis. We recognized the mucous secretion from the abdominal wall mass and performed a biopsy of the left intrahepatic bile duct tumor. On the basis of the results obstained from the biopsy, we made a diagnosis of mucinous adenocarcinoma. Percutaneous transhepatic cholangiography (FTC) revealed a fistulation between the left lateral descending branch of the intrahepatic bile duct (B3) and the abdominal wall mass. Efflux of the contrast medium from the mass was observed. Percutaneous transhepatic cholangioscopy (PTCS) disclosed a mucin-producing papillary protuberant lesion mainly in the lateral segmental branch extending to the left hepatic duct. Accordingly we made a diagnosis of mucin-producing cholangiocarcinoma complicated by abdominal wall infiltration and carried out left lobectomy. Nine months after the operation she died of cancerous peritonitis. We reported a rare case of mucin-producing cholangiocarcinoma complicated by continuous abdominal wall infiltration which we treated, together with some bibliographical comments.